Respostas
respondido por:
0
Podemos deduzir dessa PA que r = 3-1 = 2
Pela fórmula do termo geral da PA:
![a_n = a_1+(n-1)r a_n = a_1+(n-1)r](https://tex.z-dn.net/?f=a_n+%3D+a_1%2B%28n-1%29r)
Temos que:
![a_{10}=a_1+(10-1)r a_{10}=a_1+(10-1)r](https://tex.z-dn.net/?f=a_%7B10%7D%3Da_1%2B%2810-1%29r)
![a_{10}=1+9\times 2 a_{10}=1+9\times 2](https://tex.z-dn.net/?f=a_%7B10%7D%3D1%2B9%5Ctimes+2)
![\boxed{a_{10}=19} \boxed{a_{10}=19}](https://tex.z-dn.net/?f=%5Cboxed%7Ba_%7B10%7D%3D19%7D)
Espero te ajudado!
Pela fórmula do termo geral da PA:
Temos que:
Espero te ajudado!
respondido por:
1
an= a1 + (n-1)r a1 = 1 an=a10=? n=10 r=2
a10 = 1 + (10-1)2
a10 = 1+ 18
a10 = 19
{1;3;5;7;9;11;13;15;17;19}
a10 = 1 + (10-1)2
a10 = 1+ 18
a10 = 19
{1;3;5;7;9;11;13;15;17;19}
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás